SYN1 variant causes X-linked neurodevelopmental disorders: a case report of variable clinical phenotypes in siblings - Ren, Bin; Wu, Xiaoyan; Zhou, Yuqiang; Chen, Lijuan; Jiang, Jingzi (Frontiers in Neurology, 2024)
The SYN1 gene encodes synapsin I, variants within the SYN1 gene are linked to X-linked neurodevelopmental disorders with high clinical heterogeneity, with reflex epilepsies (REs) being a representative clinical manifestation. This report analyzes a Chinese pedigree affected by seizures associated with SYN1 variants and explores the genotype–phenotype correlation. The proband, a 9-year-old boy, experienced seizures triggered by bathing at the age of 3, followed by recurrent absence seizures, behavioral issues, and learning difficulties. His elder brother exhibited a distinct clinical phenotype, experiencing sudden seizures during sleep at the age of 16, accompanied by hippocampal sclerosis. Whole exome sequencing (WES) confirmed a pathogenic SYN1 variant, c.1647_1650dup (p. Ser551Argfs*134), inherited in an X-linked manner from their mother. Notably, this variant displayed diverse clinical phenotypes in the two brothers and one previously reported case in the literature. Retrospective examination of SYN1 variants revealed an association between truncating variants and the pathogenicity of REs, and non-truncating variants are more related to developmental delay/intellectual disability (DD/ID). In summary, this study contributes to understanding complex neurodevelopmental disorders associated with SYN1, highlighting the clinical heterogeneity of gene variants and emphasizing the necessity for comprehensive genetic analysis in elucidating the pathogenic mechanisms of such diseases.